1999
DOI: 10.1111/j.1469-8749.1999.tb00581.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological management of convulsive status epilepticus in children

Abstract: Convulsive status epilepticus (CSE) is the most common medical neurological emergency and continues to be associated with significant morbidity and mortality. The two primary determinants of outcome from CSE are underlying aetiology and seizure length. It is unclear whether a prolonged seizure worsens the prognosis of an underlying aetiology or whether a more severe underlying disorder is more likely to result in CSE 1 . Acceptance of the former hypothesis means that seizures need rapid treatment as their earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
1
2

Year Published

2005
2005
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 33 publications
(42 reference statements)
0
7
1
2
Order By: Relevance
“…A recent study showed that intranasal lorazepam was as effective as intramuscular paraldehyde in stopping seizures in Malawi 28 ; however, both of these agents have important drawbacks, including high cost and need for refrigeration of parenteral lorazepam and risk for sterile abscesses with intramuscular paraldehyde. 16,29 Considering available options, buccal midazolam seems to be the superior simple therapy for prolonged seizures in African children.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study showed that intranasal lorazepam was as effective as intramuscular paraldehyde in stopping seizures in Malawi 28 ; however, both of these agents have important drawbacks, including high cost and need for refrigeration of parenteral lorazepam and risk for sterile abscesses with intramuscular paraldehyde. 16,29 Considering available options, buccal midazolam seems to be the superior simple therapy for prolonged seizures in African children.…”
Section: Discussionmentioning
confidence: 99%
“…The difference between diazepam and midazolam was likely attributable to the shorter duration of action of diazepam in the brain (active half-life of diazepam: ϳ1 hour), 30 which is explained by the rapid decline in diazepam brain concentration levels during the redistribution of diazepam from cerebral gray matter into white matter, brainstem, and body fat. 14,16 The active half-life of midazolam is 2 to 3 hours in healthy children and Ͼ 5 hours in very ill children. [31][32][33] The benefits of buccal midazolam were pronounced in children who did not have malaria diagnosed at the time of presentation with seizures, but there was no difference in efficacy in children who had convulsions associated with malaria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has a particular justification when applied to tonic–clonic SE as experimental evidence shows that “decompensation” is unlikely before 30 min but becomes increasingly likely thereafter. However, because of clinical and pathophysiological evidence that tonic–clonic seizures lasting more than 5–10 min were different from shorter seizures and because it would not be appropriate to delay treatment of such seizures until 30 min, it has been argued that the “cutoff” time should be 10 or even 5 min (Scott and Neville, 1999; Chen and Wasterlain, 2006).…”
mentioning
confidence: 99%
“…Corticosteroids appear to be proconvulsant in adults with epilepsy (2,3). They are anticonvulsant, however, in children with seizure disorders such as infantile spasms and the Lennox–Gastaut syndrome (4–6). The reasons for these age‐related differences may relate to age‐dependent changes in the brain receptors that bind adrenal corticosteroids—the mineralocorticoid receptors (MRs) and glucocorticoid receptors (GRs) (7).…”
mentioning
confidence: 99%